RANCANGAN SISTEM JARINGAN STP (SPANNING TREE PROTOCOL) BERBASIS VLAN - Peniarsih, Peniarsih (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2015)
Network is used to distribute the service in the form of the Internet, IP Phone, IPTV and provide specific data connection in the building - the building, from the server, switch core, Switch distribution, distribution of media that is in use and track in use until testing. The concept of VLANs (Virtual Area Network) many advantages that can be obtained from the concept, with VLAN (Virtual Area Network), allows us to make a lot of computer networks (segmentation) and distribute only using a media distribution channels and be able to connect a local area network (LAN) without following geographical location. The growth of the Internet and computer networks that reach levels of society have been converted as a medium of communication, promotion and social networking that makes many people need the internet facility. No exception to the business world that require internet service and network connections for communications, media advertising, interconnection, and so forth. There are various problems that arise in the distribution of VLAN-VLAN that can occur because of the network that runs in a transmission medium. Problem - the problem of which Flooding, Delay, Broadcast, Network Error on the device, and which often occur death in perangkar FO Converter that will interruption in the distribution of VLAN-VLAN. Thus required the manufacture of alternative pathways (Redundant) and the appropriate use of potrocol network in order to overcome the problem of distribution.